Two new Pseudoceros (Polycladida: Pseudocerotidae) and a Prostheceraeus (Polycladida: Euryleptidae) from Andaman and Nicobar Islands, India - Dixit, Sudhanshu; Raghunathan, C.; Chandra, Kailash (Zootaxa, 2017)
Polyclads are free-living marine flatworms known for their striking colour and patterns. These animals though frequently encountered are still understudied in the Indian context. The present paper describes three new species, two belonging to the genus Pseudoceros Lang, 1884 and one to the genus Prostheceraeus Schmarda, 1859. Pseudoceros auranticrinis sp. nov. is characterised by whitish cream background colour, brown mottling with numerous white and dark brown spots all over the body except margins and a smooth dorsal surface with orange pseudotentacles, Pseudoceros vishnui sp. nov. is characterised by having purple to violet spots on dorsum with margin made up of blue spots, while Prostheceraeus fuscolineatus sp. nov. is characterised by presence of brown longitudinal lines on dorsum and black erected tentacles. This is the first description of any species under the genus Prostheceraeus from central Indo-Pacific as well as Indian Ocean. Some insights on feeding behaviour of P. vishnui sp. nov. are also provided.